2004
DOI: 10.1086/383428
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Context and the Formation of Consumer Ideals

Abstract: When a choice set consists of a distribution of alternatives with correlated benefits and costs, consumers often exhibit single-peaked preferences-they prefer an alternative having moderate costs and benefits. Theories disagree about how adding additional lower benefit/lower cost or higher benefit/higher cost alternatives to this choice set will affect relative preferences for the initial set of alternatives. Prototype theory predicts that adding alternatives should produce assimilation, whereas multiattribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Contrast of ideals may be described as occurring when the ideal point is displaced away from contextual values. Contrast of ideal-point judgments has been noted rarely in the literature (for exceptions see Cooke, Janiszewski, Cunha, Nasco, & de Wilde, 2004). Wedell et al (2005) explored socially relevant ideal-point judgments of preference for body images in a series of experiments in which participants judged the pleasantness of human figures varying in body width.…”
Section: Assimilation and Contrast For Ideal-point Judgmentsmentioning
confidence: 99%
“…Contrast of ideals may be described as occurring when the ideal point is displaced away from contextual values. Contrast of ideal-point judgments has been noted rarely in the literature (for exceptions see Cooke, Janiszewski, Cunha, Nasco, & de Wilde, 2004). Wedell et al (2005) explored socially relevant ideal-point judgments of preference for body images in a series of experiments in which participants judged the pleasantness of human figures varying in body width.…”
Section: Assimilation and Contrast For Ideal-point Judgmentsmentioning
confidence: 99%
“…One is given in a recent paper by Cooke, Janiszewski, Cunha, Nasco, and De Wilde (2004). These authors show one way to combine range-frequency scales to determine preference judgments.…”
Section: Modeling the Datamentioning
confidence: 99%
“…The attribute value at which the function peaks is referred to as an ideal point, reflecting the most pleasant attribute value (Coombs, 1964). Research exploring context effects on ideal points has primarily examined preference-related judgments in perceptual domains and has overwhelmingly found that the ideal point shifts toward the values of contextual stimuli Pettibone & Wedell, 2007;Riskey, Parducci, & Beauchamp, 1979;Wedell & Pettibone, 1999;Wedell, Santoyo & Pettibone, 2005; although for an exception, see Cooke, Janiszewski, Cunha, Nasco, & de Wilde, 2004). Panel B of Fig.…”
mentioning
confidence: 99%